COMPARATIVE STUDIES OF THE FOLK BALLAD: UKRAINIAN AND BRITISH CONTEXT - Karbashevska, О. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The establishment of comparative ballad studies in Ukraine and the USA is outlined. The analysis of the international plot “the elder sister drowns the younger one because of envy and jealousy” is performed on the material of Ukrainian and British folk ballads. The conclusion about similarities on levels of the plot, composition, images and artistic means is made. Authenticity in depicting typologically arisen events is highlighted.